Capturing the complexity of differentiated instruction. Issue 1 (2nd January 2019) - van Geel, Marieke; Keuning, Trynke; Frèrejean, Jimmy; Dolmans, Diana; van Merriënboer, Jeroen; Visscher, Adrie J.
ABSTRACT: Providing differentiated instruction (DI) is considered an important but complex teaching skill which many teachers have not mastered and feel unprepared for. In order to design professional development activities, a thorough description of DI is required. The international literature on assessing teachers' differentiation qualities describes the use of various instruments, ranging from self-reports to observation schemes and from perceived-difficulty instruments to student questionnaires. We question whether these instruments truly capture the complexity of differentiation. In order to depict this complexity, a cognitive task analysis (CTA) of the differentiation skill was performed. The resulting differentiation skill hierarchy is presented here, together with the knowledge required for differentiation, and the factors influencing its complexity. Based on the insights of this CTA, professional development trajectories can be designed and a comprehensive assessment instrument can be developed, enabling researchers and practitioners to train, assess, and monitor teaching quality with respect to providing differentiated instruction.